Histories of Knowledge in Postwar Scandinavia Actors, Arenas, and Aspirations - Östling, Johan; Olsen, Niklas; Heidenblad, David Larsson (Knowledge Societies in History, 2020)
Histories of Knowledge in Postwar Scandinavia uses case studies to explore how knowledge circulated in the different public arenas that shaped politics, economics and cultural life in and across postwar Scandinavia, particularly in the 1960s and 1970s. This book focuses on a period when the term "knowledge society" was coined and rapidly found traction. In Scandinavia, society's relationship to rational forms of knowledge became vital to the self-understanding and political ambitions of the era. Taking advantage of contemporary discussions about the circulation, arenas, forms, applications and actors of knowledge, contributors examine various forms of knowledge - economic, environmental, humanistic, religious, political, and sexual - that provide insight into the making and functioning of postwar Scandinavian societies and offer innovative studies that contribute to the development of the history of knowledge at large. The concentration on knowledge rather than the welfare state, the Cold War or the new social and political movements, which to date have attracted the lion's share of scholarly attention, ensures the book makes a historiographical intervention in postwar Scandinavian historiography. Offering a stimulating point of departure for those interested in the history of knowledge and the circulation of knowledge, this is a vital resource for students and scholars of postwar Scandinavia that provides fresh perspectives and new methodologies for exploration.